An intimate look at LET-23 EGFR trafficking in the vulval cells of live C. elegans larvae - Escobar-Restrepo, Juan M (Worm, 2014)
Precise cell fate specification is essential for organ formation. A simple view is that one or several signal sending cells emit a ligand to a group of signal receiving cells that express the corresponding receptor, which transduces the signal through intracellular enzyme pathways. All these events must be spatio-temporally regulated to achieve the proper strength, duration and output of the signaling pathways. In particular, the production and secretion of the ligand has to be coordinated with the expression and accessibility of the receptor in the signal receiving cells. Furthermore, removal of the ligand or receptor is key to achieve proper signal termination and prevent excess cell differentiation and proliferation. Improper regulation of any of these events may cause developmental defects and human disease. C. elegans is an excellent model to systematically identify genes that control the localization and activity of the Epidermal Growth Factor Receptor (EGFR) homolog LET-23. To identify regulators of LET-23 trafficking, Haag et al. observed LET-23 localization in the vulva precursor cells (VPCs) of RNAi treated larvae by live fluorescent microscopy. In this comment, we provide an overview of the newly identified regulators of LET-23 trafficking and discuss the role of the Ezrin/Radixin/Moesin homolog ERM-1 as a temporal regulator of EGFR signaling.